Ozone therapy in the treatment of recurrent vulvo-vaginitis by Candida albicans (Ozone Therapy Global Journal, 2015)
Vaginitis caused by Candida albicans is the most common gynaecological disease found in the primary health care and makes a health issue of great importance because of its high frequency. The objective of the study was to assess the effectiveness of the ozone and diet therapy treatment of recurrent vulvo vaginal by Candida albicans infections. Patients (150) were selected with ages ranging from 30 to 50 years, with vulvo-vaginitis for at least 6 months of evolution, refractory to usual drug treatment and positive cultures for candidiasis.It was performed one hydrocolontherapy with ozonized water. It was given: diet low in carbohydrates of high glucemic index, daily intravaginal instillations with ozonized water (10 sessions), daily intravaginal ozone insufflations at concentration of 20 μg/mL at speed of 0.2 L/min during 10 min (10 sessions), application of ozonized oil (OleosanR, Lacoser, Italy ) with peroxide number of 600 and 400, during 10 days, 4 major autohemotherapy at 2.0 μg once a week. At the end of treatment were repopulated the vaginal flora with Lactobacillus vaginal tablets for 7 days and repopulated the intestinal flora with lactobacillus using oral route, during 1 month. Results: 85% of patients favourably responded to treatment, 10% remained asymptomatic for a period of less than one year and 5% of patients did not respond to treatment. Intravaginal ozone therapy, offers an effective alternative to conventional treatment with usual fungicides, not only achieved a remission of symptoms and negative cultures of vaginal exudates in patients with vulvo-vaginitis, but also increased Ig A and lactobacillus in the vaginal epithelium. Also serves to restore the body´s own defence abilities by stimulating the normalization of vaginal mucosa local immunity. Without producing a disturbing effect on the saprophytes.